The Effect of Reinforcement toward Students' Speaking Ability - Herdianti Kusumawardhani; Syafrizal S; Ildi Kurniawan (Universitas Bengkulu, 2019)
This Experimental Research was conducted to find out whether reinforcement can improve the students’ speaking ability or not. The population of the research was the tenth grade students of SMAN 7 Bengkulu. The simple random sampling of the research was taken X MIPA 1 as the Experimental Group. The collection data used pre-test and post-test to see the changes of the students’ speaking score. T-test used to see the significant difference between both tests. The treatment is given to the students a set of praises as feedback in every students oral response. After doing 6 times of treatment on Experimental Group, the result indicates that reinforcement affected students speaking ability significantly. It was found that -Tcount was -18,351and -Ttable was -2,060. It means that -Ttable score was greater than -Tcount. It could be concluded that the experiment was successful because of reinforcement can improve the students’ speaking ability.